Simultaneous Occurrence of Broiler Chicken Hyper and Hypothermia In-transit and Lairage and Dead on Arrival (DOA) Index Under Tropical Climate - Freitas, Arlan S.; Carvalho, Leila M.; Soares, Adriana L.; S. Neto, Arnoud C. de; Madruga, Marta S.; Carvalho, Rafael H.; Ida, Elza I.; Shimokomaki , Massami (International Journal of Poultry Science, 2016)
Background: The pre-slaughter management conditions and transport of poultry from the farm to the slaughterhouse could represent significant economic losses compromising the animal welfare affecting consequently the meat quality if the good practices are not followed. Moreover, studies on broiler chicken journey under Brazilian tropical climate zone are scarce. Objective: The objective of this study was therefore to evaluate the influence of broiler microclimates formed in a lorry container during journey from farm to the slaughterhouse associated to lairage under commercial conditions on breast-meat quality in a tropical environment. Also, DOA index, dead on arrival was determined. Material and Methods: The broilers of 47 day-old (n = 1,400) were monitored from farm to slaughterhouse over a distance of 289 km under rainy conditions and 5 h of lairage. Anemometers were placed at 3 lorry container positions: Front, middle and rear to measure Temperature (T), Air Velocity (AV), Relative Humidity (RH) and Heat Index (HI) throughout the journey and lairage. Hyper and hypothermia were evaluated by determining the occurrence of PSE (pale, soft and exudative) and DFD (dark, firm and dry) meat. The mortality of chickens was quantified at the time the birds were hung on the receiving platform. The Tukey’s test (p≤0.05) was applied to compare means of micro-environmental data, PSE, DFD and DOA at 3 different lorry container positions. Results: The recorded AV was highest in the front and the other variables also altered depending on the container compartments location. The RH values were also the highest at the rear and lowest at the front throughout the experiment. The rainfall occurred in every journey, which might have influenced the variables, as the lorries had open roofs. The results were 10.14 and 3.59%, PSE and DFD, respectively and the DOA index was 0.45%. Conclusion: The presence of PSE and DFD meat samples indicated that the birds were micro-environmentally exposed to heat and cold stress, respectively, leading to a relatively high DOA index. All of these factors are controllable and it is advisable to encourage poultry-processing plant companies to follow good pre-slaughter management practices in order to preserve animal welfare and thus the meat quality.